Art in the Market: Action Research and Participatory Art - Bastos, Flávia; Hutzel, Karen (Informática na educação teoria & prática, 2016)
This visual essay illustrates a process of community-based art as it unfolds from our experiences in the Art in the Market program. We expect to show readers salient dimensions of this work that render it a distinguished form of participatory action research. Weaving images and text, we examine the theoretical underpinnings of this praxis and examine the often mysterious process of creating art together with a community.